2010
DOI: 10.1167/iovs.08-2988
|View full text |Cite
|
Sign up to set email alerts
|

Cirrus High-Definition Optical Coherence Tomography Compared with Stratus Optical Coherence Tomography in Glaucoma Diagnosis

Abstract: Cirrus OCT has better scan quality than Stratus OCT, especially in glaucomatous eyes. In cases with good-quality scans, the sensitivity and specificity, and AUCs were similar. The best agreement was in the global average RNFL classification. The widths of limits of agreements exceed the limits of resolution of the OCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 30 publications
2
71
0
1
Order By: Relevance
“…CpRNFL scans for assessing glaucoma do not take the full advantages offered by using SD-OCT. SD-OCT offers the ability to take wide regional RNFL measurements with high scan speed and resolution. Therefore, previous studies using the circumpapillary method for evaluating localized RNFL defects or early glaucoma detection reported similar discriminating abilities between time domain OCT and SD-OCT. 7,8,23,24 Analysis of RNFL maps is a proper way to exploit the advantages of SD-OCT. Leung et al 5 reported that a scoring system, which is designed to analyze the RNFL deviation map, significantly improves the diagnostic sensitivity for glaucoma detection at a high level of specificity when compared with cpRNFL measurements. In our study, the significance map and the thickness map showed a superior performance for detecting the localized RNFL Abbreviations: GCC, ganglion cell complex; GCL, ganglion cell layer; IPL, inner plexiform layer; NFL, nerve fiber layer; RNFL, retinal nerve fiber layer.…”
Section: Discussionmentioning
confidence: 99%
“…CpRNFL scans for assessing glaucoma do not take the full advantages offered by using SD-OCT. SD-OCT offers the ability to take wide regional RNFL measurements with high scan speed and resolution. Therefore, previous studies using the circumpapillary method for evaluating localized RNFL defects or early glaucoma detection reported similar discriminating abilities between time domain OCT and SD-OCT. 7,8,23,24 Analysis of RNFL maps is a proper way to exploit the advantages of SD-OCT. Leung et al 5 reported that a scoring system, which is designed to analyze the RNFL deviation map, significantly improves the diagnostic sensitivity for glaucoma detection at a high level of specificity when compared with cpRNFL measurements. In our study, the significance map and the thickness map showed a superior performance for detecting the localized RNFL Abbreviations: GCC, ganglion cell complex; GCL, ganglion cell layer; IPL, inner plexiform layer; NFL, nerve fiber layer; RNFL, retinal nerve fiber layer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the appearance of a new technology also implies the need of assessing its correlation with previous existing technologies. Several studies have evaluated the agreement between Cirrusand Stratus-OCT measurements in normal patients and patients with glaucoma, [16][17][18][19][20][21][22] nevertheless to our knowledge no previous studies have been published comparing RNFL thickness in patients with ON scanned with Stratus-OCT and Cirrus-OCT. As previously reported, 4-12 ON-eyes had significantly lower average RNFL thickness than fellow-eyes using both Stratus-and Cirrus-OCT (P ¼ 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…This finding has been previously mentioned by other authors in glaucoma patients. 20 Cirrus-OCT assigned more ON-eyes as abnormal based on internal normative database (44.4 vs 38%). This might be because of the higher scan resolution and more accurate data registration of this instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to measuring average cpRNFL thickness changes, it is also important to consider localized RNFL loss, in particular in the superotemporal and inferotemporal sectors, which are the most frequently regions affected in the early stages of glaucoma (Lisboa et al, 2012;Moreno-Montañés et al, 2010;Park et al, 2009;Sehi et al, 2009). cpRNFL thinning in the superotemporal and inferotemporal sectors tends to have the best diagnostic performance in early disease (Lisboa et al, 2012).…”
Section: Detecting Structural Changementioning
confidence: 99%